In silico analysis of glycosyltransferase 2 family genes in duckweed (Spirodela polyrhiza) and its role in salt stress tolerance - Jiang Mingliang (De Gruyter, 2021)
Plant glycosyltransferase 2 (GT2) family genes are involved in plant abiotic stress tolerance. However, the roles of GT2 genes in the abiotic resistance in freshwater plants are largely unknown. We identified seven GT2 genes in duckweed, remarkably more than those in the genomes of Arabidopsis thaliana, Oryza sativa, Amborella trichopoda, Nymphaea tetragona, Persea americana, Zostera marina, and Ginkgo biloba, suggesting a significant expansion of this family in the duckweed genome. Phylogeny resolved the GT2 family into two major clades. Six duckweed genes formed an independent subclade in Clade I, and the other was clustered in Clade II. Gene structure and protein domain analysis showed that the lengths of the seven duckweed GT2 genes were varied, and the majority of GT2 genes harbored two conserved domains, PF04722.12 and PF00535.25. The expression of all Clade I duckweed GT2 genes was elevated at 0 h after salt treatment, suggesting a common role of these genes in rapid response to salt stress. The gene Sp01g00794 was highly expressed at 12 and 24 h after salt treatment, indicating its association with salt stress resilience. Overall, these results are essential for studies on the molecular mechanisms in stress response and resistance in aquatic plants.